ANTIBACTERIAL ACTIVITY OF RAMBAI LEAF EXTRACT (Sonneratia caseolaris) CONCENTRATION 25% 50% 75% AND 100% AGAINST BACTERIA Enterococcus faecalis - US Ramadilla Ramadilla; Didit Aspriyanto; Sherli Diana (FKG Unlam, 2023)
ABSTRACTBackground: The causative factor of failure in the treatment of the root canal is the presence of microorganisms, namely the bacterium Enterococcus faecalis. Rambai leaf extract (Sonneratia caseolaris) also contains secondary metabolite compounds, namely, triterpenoids, phenols, tannins, steroids, and flavonoids that are able to inhibit the growth of Enterococcus faecalis bacteria which have the potential to cause failure in root canal treatment. Purpose: This research has a purpose to see the antibacterial activity of Rambai leaf extract (Sonneratia caseolaris) concentrations of 25%, 50%, 75%, and 100% against Enterococcus faecalis bacteria. Method: This study is a true experimental study designed by Posttest Only with Control Group Design using six. Material and methods: Rambai leaf extract concentrations of 25%, 50%, 75%, 100%, positive control of chlorhexidine gluconate 2%, and negative control of aqua dest was repeated 4 times. Antibacterial activity can be seen from the magnitude of the inhibitory zone formed in (MHA) Mueller Hinton Agar and BHIB (Brain Heart Infusion) using the diffusion method. Results: Based on Mann Whitney's final test, there was a significant difference in the clear zones formed around the paper disk. The average clear zone of Rambai leaf extract (Sonneratia caseolaris) concentration is 25% at 10.0mm, 50% at 12.7mm, 75% at 17.0mm, and 100% at 18.3mm. Conclusion: There is activity of Rambai leaf extract (Sonneratia caseolaris) concentrations of 25%, 50%, 75%, and 100% against Enterococcus faecalis bacteria. Keywords: Antibacterial Activity, Enterococcus faecalis, Rambai Leaf Extract